Cigarette Smoke Exposure and the Acute Respiratory Distress Syndrome*. Issue 9 (September 2015) - Calfee, Carolyn S.; Matthay, Michael A.; Kangelaris, Kirsten N.; Siew, Edward D.; Janz, David R.; Bernard, Gordon R.; May, Addison K.; Jacob, Peyton; Havel, Christopher; Benowitz, Neal L.; Ware, Lorraine B.
<x xml:space="preserve">Abstract</x> Objective: The association between cigarette smoke exposure and the acute respiratory distress syndrome in patients with the most common acute respiratory distress syndrome risk factors of sepsis, pneumonia, and aspiration has not been well studied. The goal of this study was to test the association between biomarker-confirmed cigarette smoking and acute respiratory distress syndrome in a diverse cohort. Design: Prospective cohort. Setting: Tertiary care center. Patients: Four hundred twenty-six critically ill patients with acute respiratory distress syndrome risk factors (excluding trauma and transfusion) Interventions: None. Measurements and Main Results: We obtained smoking histories and measured urine 4-(methylnitrosamino)-1-(3-pyridyl)-1- butanol (a biomarker of cigarette smoke exposure) on urine samples obtained at the time of study enrollment. The association between cigarette smoke exposure and acute respiratory distress syndrome differed based on acute respiratory distress syndrome risk factor (p < 0.02 for interaction). In patients with nonpulmonary sepsis as the primary acute respiratory distress syndrome risk factor (n = 212), 39% of those with acute respiratory distress syndrome were current smokers by history compared with 22% of those without acute respiratory distress syndrome (odds ratio, 2.28; 95% CI, 1.24–4.19; p = 0.008). Likewise, cigarette smoke exposure as measured by urine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol was significantly associated with acute respiratory distress syndrome in this group. The increased risk of acute respiratory distress syndrome in nonpulmonary sepsis was restricted to patients with 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol levels consistent with active smoking and was robust to adjustment for other acute respiratory distress syndrome predictors. Cigarette smoke exposure as measured by history or 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol was not associated with acute respiratory distress syndrome in patients with other risk factors (e.g., pneumonia and aspiration). Conclusions: Cigarette smoking measured both by history and biomarker is associated with an increased risk of acute respiratory distress syndrome in patients with nonpulmonary sepsis. This finding has important implications for tobacco product regulation and for understanding the pathogenesis of acute respiratory distress syndrome.